SOSIALISASI PENTINGNYA HIGIENE SANITASI DI PT WEIR MINERALS INDONESIA - Adolf Liku, Adolf Liku; Hardiyono; Ananta, Erwin; Luqmantoro; Setyawati, Nur Falah (EUNOIA, 2023)
Food sanitation is closely related to environmental sanitation where food products are stored, handled, produced or prepared. In the food industry, sanitation includes aseptic activities in the preparation, processing and packaging of food products, cleaning and sanitation of factories and the factory environment and worker health. Activities related to food products include quality control of raw materials, storage of raw materials, proper water supply equipment, prevention of food contamination at all stages during processing from personnel equipment, and against pests, as well as packaging and storage of the final product (Surono et al. , 2016). the conditions for implementing sanitary hygiene meet the requirements for food storage, food processing, food transportation and food storage. The level of knowledge of food handlers at PT WEIR MINERALS in food management is high regarding the quality of food that will be processed and served to workers.